1979
DOI: 10.1073/pnas.76.12.6177
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structure of pro-methionine-enkephalin: Potential enkephalin precursor from porcine hypothalamus

Abstract: A hexapeptide that we have named pro-methionine-enkephalin has been isolated from acid extracts of porcine hypothalami and found to have the amino acid sequence H-Tyr-Gly-Gly-Phe-Met(O)Arg-OH. This peptide is not a fragment of either porcine -1lipotropin or -endorphin, which suggests that it could be a precursor of [Metienkephalin in the brain by a pathway differing from the one usually postulated.The existence of still larger precursors of [Metlenkephalin, perhaps related to the recently reported a-neo-endorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 23 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…The differential effects of ions on agonist and antagonist binding also were shown to be similar to those observed in mammalian brain homogenates. These earlier studies tentatively indicated that the opiate sites are analogous to the enkephalin-type (8) receptor.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The differential effects of ions on agonist and antagonist binding also were shown to be similar to those observed in mammalian brain homogenates. These earlier studies tentatively indicated that the opiate sites are analogous to the enkephalin-type (8) receptor.…”
Section: Discussionmentioning
confidence: 90%
“…The present study not only supports these immunocytochemical observations but also di- The occurrence of both [Met]-and [LeuJenkephalin in M. edulis pedal ganglia was anticipated due to a number of reports that indirectly suggested the presence of some types of opioid compounds. Etorphine, FK 33-824, and levallorphan bind noncooperatively to a class of high-affinity sites (Kd = 1-3 nM) and cooperatively to a class of lower-affinity sites (Kd = 6-11 nM) in the pedal ganglion (8). Hill analysis of the cooperative sites revealed Hill coefficients of 2.6-3.7, indicating markedly positive homotropic cooperativity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the a-MSH did not inhibit the contractions of the mouse vas deferens at 1 MM (12). When assayed for lipolytic activity, this decapeptide failed to stimulate an increase in glycerol production in doses 4 to 4000 times greater than the effective lipolytic dose of ACTH in our system (17).…”
Section: Resultsmentioning
confidence: 99%
“…The extract corresponding to 470,000 hypothalami was the same as that used for the isolation of porcine somatostatin (3) and pro- [Met]enkephalin (4). This extract was purified first by gel filtration on Sephadex G-25 (3).…”
mentioning
confidence: 99%